The Enduring Indians of Kansas A Century and a Half of Acculturation - Herring, Joseph B. (University Press of Kansas, 1990)
The Cherokees' "Trail of Tears" and the forced migration of other Southern tribes during the 1830s and 1840s were the most notorious consequences of Andrew Jackson's Indian removal policy. Less well known is the fact that many tribes of the Old Northwest territory were also forced to surrender their lands and move west of the Mississippi River.By 1850, upwards of 10,000 displaced Indians had been settled "permanently" along the wooded streams and rivers of eastern Kansas. Twenty years later only a few hundred-mostly Kickapoos, Potawatomis, Chippewas, Munsees, Iowas, Foxes, and Sacs-remained.Joseph Herring's The Enduring Indians of Kansas recounts the struggle of these determined survivors. For them, the "end of Indian Kansas" was unacceptable, and they stayed on the lands that they had been promised were theirs forever.Offering a good counterpoint to Craig Miner's and William Unrau's The End of Indian Kansas, Herring shows the reader a shifting set of native perspectives and strategies. He argues that it was by acculturation on their own terms-by walking the fine line between their traditional ways and those of the whites-that these Indians managed to survive, to retain their land, and to resist the hostile intrusions of the white world. The story of their epic struggle to survive will place a new set of names in the pantheon of American Indian heroes.